Notary social responsibility in making deeds for disordered communities - Wahyu Andriawan; Nynda Fatmawati Octarina (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
This study aims to find out the legal provisions related to the determination of the notary's honorarium which has been regulated by law, the social responsibility of the notary in helping to make deeds for people who can't afford it, and the legal sanctions for a notary who refuses to provide services to people who can't afford it. This research is normative juridical research with a literature review approach to legislation which is analyzed qualitatively. The results of this study indicate that a notary is a state official who is authorized to provide notary services to the public in general so that he is not paid by the state, but he can collect honorarium from his client in the amount as stipulated by UUJN and also based on an agreement between the notary and his client; the notary is also obliged to provide free services to people who cannot afford to pay the honorarium because this is their obligation as stipulated in Article 37 UUJN; and a notary who refuses to provide free services to people who can't afford it, he will be subject to sanctions in the form of a written warning, temporary dismissal, honorable discharge, or dishonorable discharge.